Optimized CRISPR/Cas9-mediated in vivo genome engineering applicable to monitoring dynamics of endogenous proteins in the mouse neural tissues - Takahiko Matsuda (Nature Portfolio, 2019)
Abstract To analyze the expression, localization, and functional dynamics of target proteins in situ, especially in living cells, it is important to develop a convenient, versatile, and efficient method to precisely introduce exogenous genes into the genome, which is applicable for labeling and engineering of the endogenous proteins of interest. By combining the CRISPR/Cas9 genome editing technology with an electroporation technique, we succeeded in creating knock-in alleles, from which GFP (RFP)-tagged endogenous proteins are produced, in neurons and glial cells in vivo in the developing mouse retina and brain. Correct gene targeting was confirmed by single-cell genotyping and Western blot analysis. Several gene loci were successfully targeted with high efficiency. Moreover, we succeeded in engineering the mouse genome to express foreign genes from the endogenous gene loci using a self-cleaving 2A peptide. Our method could be used to monitor the physiological changes in localization of endogenous proteins and expression levels of both mRNA and protein at a single cell resolution. This work discloses a powerful and widely applicable approach for visualization and manipulation of endogenous proteins in neural tissues.